Pemberdayaan TPQ Al Ishmah guna Meningkatkan Kembali Nilai Islam di Desa Tinggarjaya - Akhmad Ainun Naji; Intan Nur Azizah (JPPMI: Jurnal Pelayanan dan Pemberdayaan Masyarakat Indonesia, 2026)
Community service certainly cannot be separated from the impact that the community wants to feel, either directly or indirectly. The value of Islam is felt to be decreasing along with the Covid-19 pandemic that has hit the whole world, especially in Indonesia. Empowerment of TPQ or other places of worship is aimed at increasing religious values, especially Islam in the community. The method used in this paper is descriptive qualitative with data collection techniques in the form of literature and field studies. It started with a discussion with the Village Head and religious leaders, then counseling and socialization about worship, simulation and evaluation of activities as well as monitoring of worship and muamalah activities. The purpose of this assistance is none other than to increase the value of Islam, both in terms of worship and muamalah. The empowerment of TPQ or places of worship as a center of activity as well as increasing Islamic values is strongly supported by the surrounding community, because it has a positive impact on the community and the surrounding environment